A sponge quilt resistant to pulling and washing and a preparation method thereof

CN122911274APending Publication Date: 2026-10-16QINGDAO SHANGYA HOUSEWARE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611294477.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而将海绵材料直接作为被子填充物仍面临诸多技术难题:常规海绵切割成薄片后强度不足、易撕裂,多层海绵之间缺乏有效结合力,洗涤时层间易滑移堆叠,海绵开孔结构使液态水易滞留其中,水洗后难以脱水干燥

Benefits of technology

第一,本发明海绵薄片配方中加入疏水剂,使海绵开孔孔壁具备疏水特性,水洗时水分不易在孔壁表面附着滞留,有利于快速脱水,最外侧两层采用30~60D高密度弹性海绵提供良好支撑和回弹性,中间层采用18~40D低密度海绵提供柔软贴合感,梯度密度设计使被子兼具支撑性和舒适性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of household articles, and discloses a sponge quilt resistant to pulling and washing, which comprises a quilt cover fabric and a filling core filled in the quilt cover fabric, the filling core is composed of at least two layers of sponge sheets and interlayer bonding layers arranged between adjacent sponge sheets, the thickness of a single layer of the sponge sheet is 5-20 mm, the interlayer bonding layer is a porous low-density composite fiber, the thickness of the interlayer bonding layer is 2-5 mm, and the pore size of the interlayer bonding layer is 10-50 microns. The sponge sheet formula of the present application is added with a hydrophobic agent, so that the sponge opening hole wall has hydrophobic properties, water is not easy to adhere and stay on the surface of the hole wall during washing, which is beneficial to rapid dehydration, and the gradient density design makes the quilt have both support and comfort; the interlayer bonding layer adopts a closed polyurethane foaming system reinforced by cotton fibers, and after being heated, cross-linked and solidified, the interlayer bonding layer forms a porous low-density composite fiber layer, and realizes firm combination through the dual effects of chemical cross-linking bonding and physical insertion anchoring, thereby effectively solving the technical problem of interlayer slippage and stacking of the multi-layer sponge during machine washing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of household goods technology, and in particular to a tensile-resistant and water-resistant sponge quilt and its preparation method. Background Technology

[0002] As a daily necessity, the choice of filling material for quilts directly affects sleep quality and physical health. Currently, quilts on the market are mainly classified into several categories according to their filling materials, including down quilts, synthetic fiber quilts, cotton quilts, and silk quilts. However, each of these traditional quilts has its own insurmountable technical defects.

[0003] The application of sponge (polyurethane foam) materials in mattresses and pillows is already very mature. Its open-cell structure gives the material excellent pressure dispersion, energy absorption and cushioning properties, and breathability. However, using sponge materials directly as quilt filling still faces many technical challenges: conventional sponges lack strength and are easily torn when cut into thin sheets; multi-layered sponges lack effective bonding force, and the layers tend to slip and stack during washing; the open-cell structure of the sponge makes it easy for liquid water to remain inside, making it difficult to dehydrate and dry after washing. Summary of the Invention

[0004] To address the problems existing in sponge quilts, in the first aspect, the present invention provides a tensile and water-resistant sponge quilt, comprising a quilt cover fabric and a filling core inside the quilt cover fabric. The filling core is composed of at least two layers of sponge sheets and an interlayer bonding layer disposed between adjacent sponge sheets, which are alternately stacked. The thickness of a single layer of sponge sheet is 5~20mm. The interlayer bonding layer is a porous low-density composite fiber layer with a thickness of 2~5mm and a pore size of 10~50μm.

[0005] The two outermost foam sheets are made of 30-60D elastic foam, while the middle foam sheet is made of 18-40D low-density foam. This structural design provides good support and resilience on both sides of the quilt, while the middle layer offers a soft and snug fit, comprehensively enhancing the quilt's enveloping experience.

[0006] In this invention, the sponge sheet is made of polyurethane and is composed of the following components by weight: 80-120 parts of polyether polyol with a hydroxyl value of 42-56 mgKOH / g, 15-35 parts of polymer polyol with a solid content of 40%-45%, 35-55 parts of toluene diisocyanate, 2.5-4.5 parts of water, 3-8 parts of physical foaming agent, 0.8-2 parts of silicone oil surfactant, 0.15-0.4 parts of amine catalyst, 0.1-0.3 parts of tin catalyst, 0.5-1.5 parts of crosslinking agent, 0.5-2 parts of chain extender, 0.3-1 part of hydrolytic stabilizer, and 1-3 parts of hydrophobic agent. The addition of a hydrophobic agent to the sponge formulation reduces the surface energy of the inner wall of the sponge pores, making it less likely for water to adhere and remain on the surface of the sponge pores, thus facilitating rapid drainage and dehydration after washing.

[0007] Specifically, the physical foaming agent is selected from any one of cyclopentane, n-pentane, isopentane, or HFC-245fa; the crosslinking agent is selected from any one of diethanolamine, triethanolamine, or glycerol; the chain extender is selected from any one of ethylene glycol, 1,4-butanediol, or diethylene glycol; the hydrolytic stabilizer is selected from any one of carbodiimide compounds or polycarbodiimide; and the hydrophobic agent is selected from any one of polysiloxane hydrophobic agents, fluorinated alkyl acrylate copolymers, or metal stearate salts.

[0008] In this invention, the interlayer bonding layer is composed of the following substances in parts by weight: 100 parts of water-dispersible closed-cell polyurethane prepolymer emulsion (solid content 40%~50%), 10~30 parts of cotton fiber (length 1~5mm), 3~8 parts of azodicarbonamide foaming agent, 5%~15% of zinc oxide foaming activator (added amount is 5%~15% of the weight of azodicarbonamide foaming agent), 5~15 parts of micronized superabsorbent resin microparticles (particle size 10~50μm), 3~12 parts of β-cyclodextrin, 0.5~2 parts of nonionic surfactant, 0.3~1 part of hydrolytic stabilizer, and 0.2~0.5 parts of rheology modifier.

[0009] In the interlayer bonding layer formulation, the addition of cotton fibers not only strengthens and toughens the structure, but their natural hydrophilicity also endows the bonding layer with excellent moisture absorption and wicking properties. β-Cyclodextrin has a ring-shaped cavity structure with an external hydrophilic and internal hydrophobic properties. The hydroxyl groups on the outer wall of its molecules can form hydrogen bonds with water molecules, enhancing the water-collecting capacity of the bonding layer. At the same time, its cavity structure can encapsulate gas molecules generated by the decomposition of the foaming agent, stabilizing bubbles and refining pore size, resulting in more uniform foam pore size. Micronized superabsorbent resin particles provide moisture enrichment, enriching free water in the sponge pore structure to the bonding layer region. Cotton fibers further provide lateral moisture conduction channels. The three work synergistically to construct a complete drainage pathway of "hydrophobic desorption from the sponge pore wall - hydrophilic enrichment in the bonding layer - lateral conduction by cotton fibers," fundamentally solving the problem of moisture retention in sponge fillers.

[0010] Specifically, the micronized superabsorbent resin particles are selected from any one of starch-grafted acrylate copolymers, cellulose-grafted acrylamide copolymers, or polyacrylate superabsorbent resins; the nonionic surfactant is selected from any one of alkylphenol polyoxyethylene ethers, fatty alcohol polyoxyethylene ethers, or sorbitan fatty acid esters; the hydrolytic stabilizer is a carbodiimide hydrolytic stabilizer; and the rheology modifier is any one of hydrophobically modified alkali-swellable acrylate thickeners or polyurethane associative thickeners.

[0011] Secondly, the present invention also provides a method for preparing the above-mentioned tensile and water-resistant quilt, comprising the following steps: (1) Preparation of sponge sheets: Weigh the raw materials according to the above formula, mix the other components except for toluene diisocyanate and physical foaming agent evenly, add physical foaming agent and stir for 30~60s, finally add toluene diisocyanate and stir at high speed of 4500~6000rpm for 3~8s, pour into mold for foaming, and cure at 70℃~80℃ for 4~8h. Cut the cured block sponge into sheets with a thickness of 5~20mm on a horizontal slicer. The foaming process parameters are: raw material temperature 22℃~26℃, mold temperature 35℃~45℃, milky whitening time 8~14s, and rising time 75~110s.

[0012] (2) Preparation of interlayer bonding paste precursor: Weigh each component according to the above formula, put the water-dispersible closed polyurethane prepolymer emulsion into a stirring container, and add cotton fiber, micronized superabsorbent resin microparticles, β-cyclodextrin, nonionic surfactant, hydrolysis stabilizer and rheology modifier in sequence under room temperature conditions. Finally, add azodicarbonamide foaming agent and zinc oxide foaming activator, and stir at a low speed of 40~80 rpm for 20~30 min to form a uniform paste.

[0013] (3) Coating and stacking pre-forming: Coating the paste precursor obtained in step (2) onto the upper surface of the first layer of sponge sheet with a coating amount of 200~400g / m² and a coating thickness of 1~3mm. Cover with the second layer of sponge sheet and apply a pressure of 0.01~0.03MPa to press. If there are multiple layers, repeat the above operation until all sponge sheets are stacked. Let stand at room temperature for 10~20min to complete the pre-forming.

[0014] (4) Heating and curing: The stacked preform obtained in step (3) is heated to 110℃~130℃ and held for 10~20min to allow the closed polyurethane prepolymer to undergo a desealing and crosslinking reaction. At the same time, the azodicarbonamide foaming agent is heated and decomposed to form a uniform foam. After cooling, a multilayer sponge composite filling core is obtained. The heating is divided into two stages: the first stage is held at 60℃~80℃ for 5~8min to allow the paste precursor to penetrate and wet the open pores on the surface of the sponge; the second stage is heated to 110℃~130℃ and held for 10~20min to simultaneously complete the crosslinking curing and foaming. After heating and curing, the multilayer composite is cooled to 30℃~40℃ under a pressure of 0.01~0.05MPa to perform a shaping treatment.

[0015] (5) Filling and quilting fixation: The multi-layer sponge composite filling core obtained in step (4) is inserted into the shell made of quilt cover fabric and fixed by single-needle quilting with a quilting spacing of 15~30cm to obtain a tensile and water-resistant sponge quilt.

[0016] The beneficial effects of this invention are as follows: First, the sponge sheet formula of this invention incorporates a hydrophobic agent, which gives the pore walls of the sponge hydrophobic properties. During washing, water is less likely to adhere to and remain on the pore wall surface, which is conducive to rapid dehydration. The outermost two layers use 30~60D high-density elastic sponge to provide good support and resilience, while the middle layer uses 18~40D low-density sponge to provide a soft and comfortable feel. The gradient density design makes the quilt both supportive and comfortable.

[0017] Secondly, the interlayer bonding layer of this invention adopts a closed polyurethane foam system reinforced with cotton fibers. After heating and cross-linking curing, it forms a porous low-density composite fiber layer. The bonding layer and the sponge layer are firmly bonded through the dual effects of chemical cross-linking bonding and physical interpenetration anchoring, which effectively solves the technical problem of interlayer slippage and stacking of multi-layer sponges during machine washing. At the same time, the addition of β-cyclodextrin refines the foam pore size, making the bonding layer structure more uniform.

[0018] Third, this invention constructs a complete drainage pathway of "hydrophobic desorption from the sponge pore walls - hydrophilic enrichment in the binding layer - lateral conduction by cotton fibers". The hydrophobic agent in the sponge formulation makes it difficult for water to adhere to the pore walls; the highly absorbent resin particles in the binding layer enrich free water in the binding layer; the hydroxyl groups on the outer wall of β-cyclodextrin enhance the water collection capacity; and the cotton fibers provide lateral water conduction channels. The three work together to enable the sponge to be quickly dehydrated and dried after machine washing.

[0019] Fourth, this invention combines the two functional steps of interlayer bonding and self-pore creation into one through an integrated process of in-situ cross-linking and foaming of a foamable paste precursor between sponge layers. The process is simplified, efficient, and suitable for large-scale industrial production. Detailed Implementation

[0020] The present invention will be described below with reference to examples. These examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Example 1

[0021] A tensile and water-resistant sponge quilt includes a quilt cover fabric and a filling core inside the quilt cover fabric. The filling core is composed of four layers of sponge sheets and interlayer bonding layers disposed between adjacent sponge sheets, stacked alternately in the following manner: sponge sheet - interlayer bonding layer - sponge sheet - interlayer bonding layer - sponge sheet - interlayer bonding layer - sponge sheet; wherein, each sponge sheet is 15mm thick, the two outermost sponge sheets are 50D elastic sponge, the middle sponge sheet is 30D low-density sponge, and the interlayer bonding layer is a porous low-density composite fiber with a thickness of 4mm and a pore size of 30μm; the total thickness of the filling core is 72mm.

[0022] The sponge sheet is made of polyurethane. The 50D elastic sponge is composed of the following components by weight: 110 parts of glycerol-based polyether triol with a hydroxyl value of 50 mg KOH / g, 25 parts of polymer polyol (Dow VORALUX HL 431) with a solid content of 43%, 40 parts of toluene diisocyanate, 3.5 parts of water, 4 parts of cyclopentane blowing agent, 1.2 parts of silicone oil surfactant, 0.3 parts of N,N-dimethylcyclohexylamine catalyst, 0.2 parts of dibutyltin dilaurate catalyst, 1 part of triethanolamine crosslinking agent, 1.1 parts of 1,4-butanediol chain extender, 0.6 parts of carbodiimide hydrolysis stabilizer, 0.4 parts of antioxidant, and 2 parts of polydimethylsiloxane hydrophobic agent. The 30D low-density sponge is composed of the following components by weight: 110 parts of glycerol-based polyether triol with a hydroxyl value of 50 mg KOH / g, 25 parts of polymer polyol (Dow VORALUX HL 431) with a solid content of 43%. 431) 25 parts, toluene diisocyanate 38 parts, water 4.5 parts, cyclopentane foaming agent 6 parts, silicone oil surfactant 1.2 parts, N,N-dimethylcyclohexylamine catalyst 0.3 parts, dibutyltin dilaurate catalyst 0.2 parts, triethanolamine crosslinking agent 1 part, 1,4-butanediol chain extender 1.1 parts, carbodiimide hydrolysis stabilizer 0.6 parts, antioxidant 0.4 parts, polydimethylsiloxane hydrophobic agent 1.5 parts.

[0023] The interlayer bonding layer is composed of the following substances in parts by weight: 100 parts of water-dispersible closed-type polyurethane prepolymer emulsion (solid content 45%); 20 parts of cotton fiber (length 3mm); 5 parts of azodicarbonamide foaming agent; 0.5 parts of zinc oxide foaming activator; 10 parts of starch-grafted acrylate copolymer (particle size 25μm); 8 parts of β-cyclodextrin; 1.2 parts of alkylphenol polyoxyethylene ether; 0.6 parts of carbodiimide hydrolysis stabilizer; and 0.3 parts of polyurethane associative thickener.

[0024] The preparation method of the tensile and water-resistant sponge blanket in this embodiment is as follows: (1) Preparation of sponge sheets: Foaming raw materials for 50D outer layer sponge and 30D middle layer sponge were prepared separately. All components except toluene diisocyanate and cyclopentane were added to the mixing vessel in sequence and stirred at 1200 rpm for 15 min at 25℃ to obtain white material composition. Cyclopentane was added to the white material composition and stirring was continued for 45 s. Finally, toluene diisocyanate was added and stirred at 5000 rpm for 5 s immediately. The mixture was quickly poured into the mold, and the mold temperature was controlled at 40℃. The material was allowed to foam and rise freely. The milky whitening time was controlled at 10~12 s and the rising time at 85~95 s. After foaming, the foam was removed from the mold and cured in an oven at 75℃ for 6 h. The cured block sponge was cut into sheets with a thickness of 15 mm on a horizontal slicer, and the cutting thickness tolerance was controlled within ±0.3 mm. Two sheets of outer layer sponge and two sheets of middle layer sponge were cut.

[0025] (2) Surface activation treatment of sponge sheet: The sponge sheet obtained in step (1) is passed through an atmospheric pressure plasma treatment device at a linear speed of 10 m / min and a treatment power of 2 kW to uniformly treat both sides of the sponge sheet.

[0026] (3) Preparation of interlayer bonded paste precursor: Weigh each component according to the formula amount, add the water-dispersible closed polyurethane prepolymer emulsion into a planetary mixer, and stir at 60 rpm at room temperature. Then add cotton fiber, starch-grafted acrylate copolymer superabsorbent resin microparticles, β-cyclodextrin, alkylphenol polyoxyethylene ether nonionic surfactant, carbodiimide hydrolysis stabilizer, and polyurethane associative thickener in sequence. Finally, add azodicarbonamide foaming agent and zinc oxide foaming activator. After all the materials are added, continue stirring at 60 rpm for 25 min to ensure that the components are fully mixed and uniform, forming a fine and uniform paste. The viscosity of the paste was measured to be 92000 cP (Brookfield RVDV-II type rotational viscometer, rotor No. 4, 12 rpm, 25℃).

[0027] (4) Coating and Stacking Pre-forming: Take the first layer of 50D outer layer sponge sheet and lay it flat on the workbench. Use a scraping method to evenly coat the paste precursor prepared in step (3) onto the upper surface of the sponge sheet. The coating amount is 300g / m². 2 The coating thickness is approximately 2 mm. After coating, the first 30D intermediate layer sponge sheet is placed on top of the coated layer, and a uniform pressure of 0.02 MPa is applied and held for 8 seconds to ensure tight adhesion between the two sponge sheets and the intermediate paste layer. The coating and covering operations are repeated, sequentially stacking the second 30D intermediate layer sponge sheet and the final 50D outer layer sponge sheet, forming an alternating stacked structure of 3 interlayer bonding layers and 4 sponge sheets. After all layers are stacked, they are allowed to mature at room temperature for 15 minutes, utilizing the adhesiveness of the paste to achieve initial positioning and fixation between the layers.

[0028] (5) Heating crosslinking and simultaneous foaming and pore formation: The multilayer body pre-shaped by room temperature stacking in step (4) is sent into a hot air circulating drying tunnel for heating treatment. The heating is divided into two stages: the first stage drying tunnel temperature is set at 75℃ and held for 6 minutes to reduce the viscosity of the paste precursor and fully penetrate into the pores of the sponge sheet, with a penetration depth of about 20% of the thickness of the sponge sheet; the second stage drying tunnel temperature is raised to 120℃ and held for 15 minutes. During the holding process, saturated water vapor is introduced into the drying tunnel to maintain the relative humidity of the environment at 70%. Under these conditions, the closed groups in the closed polyurethane prepolymer are unsealed, releasing active isocyanate groups, which undergo chemical grafting reaction with the active hydrogen on the surface of the sponge pore wall. At the same time, crosslinking and chain extension occur between the prepolymer molecular chains to form a three-dimensional network structure. Meanwhile, the azodicarbonamide foaming agent decomposes under heat, releasing uniform nitrogen bubbles, which form a uniform porous structure in situ inside the interlayer bonding layer.

[0029] (6) Compression and Cooling: After the heating and curing in step (5) is completed, the multilayer composite is taken out from the drying tunnel and sent to the flattening and shaping machine, where it is cooled to 35°C under a pressure of 0.03 MPa by air cooling. After cooling, a multilayer sponge composite filler core is produced, with a total thickness of 72 mm and a total weight of 1680 g. Visual inspection shows that the layers of the filler core are tightly bonded, with no visible peeling or bubble aggregation defects. The filler core is then subjected to a second curing treatment at 45°C for 5 hours to further enhance the degree of crosslinking reaction.

[0030] (7) Fabric cutting and sewing: Double-sided knitted fabric with a weight of 220g / m² is selected. 2 The fabric is composed of 70% cotton, 10% spandex, and 20% polyester fiber. It has undergone hydrophilic softening and antibacterial / anti-mite treatments. Cut the fabric into one upper piece and one lower piece, each measuring 206cm x 236cm (including seam allowance). Sew the three edges of the upper and lower pieces together with a straight seam, with a seam width of 1.2cm, leaving one edge as an opening for filling.

[0031] (8) Filling and Quilting Fixing: Insert the multi-layer sponge composite filling core obtained in step (6) into the duvet cover shell through the opening in step (7), lay it flat, and ensure that the four corners and edges are accurately aligned. Sew the opening closed with a flat stitch. Use a single-needle quilting machine to perform diamond quilting with a quilting spacing of 20cm. The quilting stitches run through the top layer fabric, the multi-layer sponge composite filling core, and the bottom layer fabric. High-strength polyester sewing thread with a linear density of 25tex is used for quilting.

[0032] (9) Edge binding and finished product inspection: The edges of the quilted quilt are bound with a width of 2.5cm, and the binding is completed in one go using a double-needle binding sewing machine. The finished product is inspected and found to be 200cm×230cm in size and 2210g in weight. It has a smooth and wrinkle-free appearance, uniform quilting stitches, and no displacement of the filling core. Example 2

[0033] A tensile and washable sponge quilt includes a quilt cover fabric and a filling core inside the quilt cover fabric. The filling core is composed of three layers of sponge sheets and interlayer bonding layers disposed between adjacent sponge sheets, stacked alternately in the following manner: sponge sheet - interlayer bonding layer - sponge sheet - interlayer bonding layer - sponge sheet. The thickness of each sponge sheet is 20mm. The two outermost sponge sheets are 60D elastic sponge, and the middle sponge sheet is 40D low-density sponge. The interlayer bonding layer is a porous low-density composite fiber layer with a single layer thickness of 5mm and an average pore size of 50μm. The total thickness of the filling core is 70mm.

[0034] The sponge sheet is made of polyurethane. The 60D elastic sponge is composed of the following parts by weight: 120 parts of polyether polyol (DOW VORANOL CP 3322) with a hydroxyl value of 56 mg KOH / g, 35 parts of polymer polyol (Dow VORALUX HN 394) with a solid content of 45%, 55 parts of toluene diisocyanate, 3.0 parts of water, 5 parts of n-pentane foaming agent, 2 parts of silicone oil surfactant (L-580), 0.4 parts of bis(dimethylaminoethyl) ether catalyst, 0.3 parts of stannous octoate catalyst, 1.5 parts of diethanolamine crosslinking agent, 2 parts of ethylene glycol chain extender, 1 part of polycarbodiimide hydrolysis stabilizer, 0.6 parts of antioxidant (Irganox 1010), and 3 parts of fluorinated alkyl acrylate copolymer hydrophobic agent. The 40D low-density sponge is composed of the following parts by weight: polyether polyol (DOW VORANOL CP 3322) with a hydroxyl value of 56 mg KOH / g. 3322) 120 parts, polymer polyol (Dow VORALUX HN 394) with a solid content of 45% 35 parts, toluene diisocyanate 52 parts, water 4.0 parts, n-pentane foaming agent 7 parts, silicone oil surfactant (L-580) 2 parts, bis(dimethylaminoethyl) ether catalyst 0.4 parts, stannous octoate catalyst 0.3 parts, diethanolamine crosslinking agent 1.5 parts, ethylene glycol chain extender 2 parts, polycarbodiimide hydrolysis stabilizer 1 part, antioxidant (Irganox 1010) 0.6 parts, fluorinated alkyl acrylate copolymer hydrophobic agent 2 parts.

[0035] The interlayer bonding layer is composed of the following components by weight: 100 parts of water-dispersible closed-type polyurethane prepolymer emulsion (50% solid content); 30 parts of cotton fiber (5mm in length); 8 parts of azodicarbonamide foaming agent; 1.2 parts of zinc oxide foaming activator; 15 parts of cellulose-grafted acrylamide copolymer superabsorbent resin microparticles (50μm in particle size); 12 parts of β-cyclodextrin; 2 parts of fatty alcohol polyoxyethylene ether nonionic surfactant; 1 part of polycarbodiimide hydrolysis stabilizer; and 0.5 parts of hydrophobic modified alkali-swellable acrylate thickener.

[0036] The preparation method of the tensile and water-resistant sponge quilt in this embodiment includes the following steps: (1) Preparation of sponge sheets: Foaming raw materials for 60D outer layer sponge and 40D middle layer sponge were prepared separately. All components except toluene diisocyanate and n-pentane were added to the mixing vessel in sequence and stirred at 1500 rpm for 15 min at 26℃ to obtain white material mixture. n-pentane was added to the white material mixture and stirring was continued for 60 s. Finally, toluene diisocyanate was added and stirred at 6000 rpm for 8 s immediately. The mixture was quickly poured into the mold, and the mold temperature was controlled at 45℃. The material was allowed to foam and rise freely. The milky whitening time was controlled at 12~14 s and the rising time at 100~110 s. After foaming, the foam was removed from the mold and cured in an oven at 80℃ for 8 h. The cured block sponge was cut into 20 mm thick sheets on a horizontal slicer, and the cutting thickness tolerance was controlled within ±0.3 mm. Two outer layer sponge sheets were cut and one middle layer sponge sheet was cut.

[0037] (2) Surface activation treatment of sponge sheets: The sponge sheets obtained in step (1) are passed through an atmospheric pressure plasma treatment device at a linear velocity of 15 m / min and a treatment power of 3 kW to uniformly treat both sides of the sponge sheets. After plasma treatment, the surface of the sponge sheets is simultaneously treated with γ-aminopropyltriethoxysilane coupling agent by atomization spraying at a spraying amount of 1.5 g / m. 2 .

[0038] (3) Preparation of interlayer bonding paste precursor: Weigh each component according to the formula amount, add the water-dispersible closed polyurethane prepolymer emulsion into a planetary mixer, stir at 80 rpm at room temperature, and add cotton fiber, cellulose grafted acrylamide copolymer superabsorbent resin microparticles, β-cyclodextrin, fatty alcohol polyoxyethylene ether nonionic surfactant, polycarbodiimide hydrolysis stabilizer and hydrophobically modified alkali-swellable acrylate thickener in sequence, and finally add azodicarbonamide foaming agent and zinc oxide foaming activator. After all the materials are added, continue stirring at 80 rpm for 30 min to ensure that all components are fully mixed and uniform, forming a fine and uniform paste.

[0039] (4) Coating and Stacking Pre-forming: Take the first layer of 60D outer layer sponge sheet and lay it flat on the workbench. Use a scraping method to evenly coat the paste precursor prepared in step (3) onto the upper surface of the sponge sheet. The coating amount is 400g / m². 2 The coating thickness is approximately 3 mm. After coating, a 40D intermediate layer sponge sheet is placed on top of the coating layer, and a uniform pressure of 0.03 MPa is applied and held for 10 seconds. The above coating and covering operations are repeated, and the final 60D outer layer sponge sheet is stacked on top, forming an alternating stacked structure of 2 interlayer bonding layers and 3 sponge sheets. After all stacking is completed, the structure is left to age at room temperature for 20 minutes to complete the pre-forming process.

[0040] (5) Heating crosslinking and simultaneous foaming and pore formation: The multilayer body pre-shaped by room temperature stacking in step (4) is sent into a hot air circulating oven for heating treatment. The oven temperature in the first stage is set at 80°C and held for 8 minutes; in the second stage, the oven temperature is raised to 130°C and held for 20 minutes. During the holding process, saturated water vapor is introduced into the oven to maintain the relative humidity of the environment at 80%. Under these conditions, crosslinking curing and foaming and pore formation are completed simultaneously.

[0041] (6) Compression and Cooling: After the heating and curing in step (5) is completed, the multilayer composite is taken out from the drying tunnel and sent to the flattening and shaping machine, where it is cooled to 40°C by air cooling under a pressure of 0.05MPa. After cooling, a multilayer sponge composite filling core is produced, with a total thickness of 70mm. The filling core is then subjected to a second curing treatment at 50°C for 6 hours.

[0042] (7) Fabric cutting and sewing: Warp-knitted elastic fabric with a weight of 280g / m² is selected. The composition is 70% nylon and 30% spandex. The fabric has been treated with moisture-wicking and antibacterial and anti-mite treatments. Cut the fabric into one upper piece and one lower piece, with a size of 156cm×216cm (including seam allowance). Sew the three sides of the upper and lower pieces together with a flat seam with a seam width of 1.5cm, leaving one side as an opening for filling.

[0043] (8) Filling and quilting fixation: The multi-layer sponge composite filling core obtained in step (6) is inserted into the duvet cover shell, laid flat, with accurate corner alignment, and the opening is sewn closed. A single-needle quilting machine is used to perform square quilting with a quilting spacing of 30cm. High-strength polyester sewing thread with a linear density of 30tex is used for quilting.

[0044] (9) Edge binding and finished product inspection: The edges of the quilted quilt are bound with a binding width of 3cm. The finished product is inspected and found to be 150cm×210cm in size, with a smooth appearance and even quilting stitches. Example 3

[0045] A tensile and washable sponge quilt includes a quilt cover fabric and a filling core inside the quilt cover fabric. The filling core is composed of five layers of sponge sheets and interlayer bonding layers disposed between adjacent sponge sheets, stacked alternately in the following manner: sponge sheet - interlayer bonding layer - sponge sheet - interlayer bonding layer - sponge sheet - interlayer bonding layer - sponge sheet - interlayer bonding layer - sponge sheet; wherein, the thickness of a single layer of sponge sheet is 5mm, the outermost two sponge sheets are 30D elastic sponge, the middle three layers of sponge sheets are 18D low-density sponge, and the interlayer bonding layer is a porous low-density composite fiber layer with a single layer thickness of 2mm and an average pore size of 10μm; the total thickness of the filling core is 33mm.

[0046] The sponge sheet is made of polyurethane. The 30D elastic sponge is composed of the following components by weight: 80 parts of polyether polyol (DOW VORANOL 2070) with a hydroxyl value of 42 mg KOH / g, 15 parts of polymer polyol (DOW VORALUXHL 400) with a solid content of 40%, 35 parts of toluene diisocyanate, 2.5 parts of water, 3 parts of isopentane foaming agent, 0.8 parts of silicone oil surfactant (B-8715LF), 0.15 parts of pentamethyldiethylenetriamine catalyst, 0.1 parts of dimethyltin dithiolate catalyst, 0.5 parts of glycerol crosslinking agent, 0.5 parts of diethylene glycol chain extender, 0.3 parts of carbodiimide hydrolysis stabilizer (Stabaxol P), 0.2 parts of antioxidant (Irganox 5057), and 1.5 parts of zinc stearate hydrophobic agent. The 18D low-density sponge is composed of the following components by weight: hydroxyl value of 42 mg KOH / g... 80 parts of KOH / g polyether polyol (DOW VORANOL 2070), 15 parts of polymer polyol with 40% solid content (DOW VORALUX HL 400), 32 parts of toluene diisocyanate, 3.5 parts of water, 5 parts of isopentane foaming agent, 0.8 parts of silicone oil surfactant (B-8715 LF), 0.15 parts of pentamethyldiethylenetriamine catalyst, 0.1 parts of dimethyltin dithiolate catalyst, 0.5 parts of glycerol crosslinking agent, 0.5 parts of diethylene glycol chain extender, 0.3 parts of carbodiimide hydrolysis stabilizer (StabaxolP), 0.2 parts of antioxidant (Irganox 5057), and 1.0 part of zinc stearate hydrophobic agent.

[0047] The interlayer bonding layer is composed of the following substances in parts by weight: 100 parts of water-dispersible closed-type polyurethane prepolymer emulsion (solid content 40%); 10 parts of cotton fiber (length 1mm); 3 parts of azodicarbonamide foaming agent; 0.15 parts of zinc oxide foaming activator; 5 parts of sodium polyacrylate superabsorbent resin microparticles (particle size 10μm); 3 parts of β-cyclodextrin; 0.5 parts of dehydrated sorbitan fatty acid ester nonionic surfactant (Span-80); 0.3 parts of carbodiimide hydrolysis stabilizer; and 0.2 parts of hydrophobically modified alkali-swellable acrylate thickener (ASE-60).

[0048] The preparation method of the tensile and water-resistant sponge quilt in this embodiment includes the following steps: (1) Preparation of sponge sheets: Foaming raw materials for 30D outer layer sponge and 18D middle layer sponge were prepared separately. All components except toluene diisocyanate and isopentane were added to the mixing vessel in sequence and stirred at 1000 rpm for 15 min at 22℃ to obtain white material mixture. Isopentane was added to the white material mixture and stirring was continued for 30 s. Finally, toluene diisocyanate was added and stirred at 4500 rpm for 3 s immediately. The mixture was quickly poured into the mold, and the mold temperature was controlled at 35℃. The material was allowed to foam and rise freely. The milky whitening time was controlled at 8~10 s and the rising time at 75~85 s. After foaming, the foam was removed from the mold and cured in an oven at 70℃ for 4 h. The cured block sponge was cut into sheets with a thickness of 5 mm on a horizontal slicer, and the cutting thickness tolerance was controlled within ±0.3 mm. Two sheets of outer layer sponge and three sheets of middle layer sponge were cut.

[0049] (2) Surface activation treatment of sponge sheet: The sponge sheet obtained in step (1) is passed through an atmospheric pressure plasma treatment device at a linear speed of 5 m / min and a treatment power of 1 kW to uniformly treat both sides of the sponge sheet.

[0050] (3) Preparation of interlayer bonding paste precursor: Weigh each component according to the formula amount, add the water-dispersible closed polyurethane prepolymer emulsion into a planetary mixer, and stir at 40 rpm at room temperature. Then add cotton fiber, sodium polyacrylate superabsorbent resin microparticles, β-cyclodextrin, dehydrated sorbitan fatty acid ester nonionic surfactant, carbodiimide hydrolysis stabilizer, and hydrophobically modified alkali-swellable acrylate thickener in sequence. Finally, add azodicarbonamide foaming agent and zinc oxide foaming activator. After all the materials are added, continue stirring at 40 rpm for 20 min to ensure that all components are fully mixed and uniform, forming a fine and uniform paste.

[0051] (4) Coating and Stacking Pre-forming: Take the first layer of 30D outer layer sponge sheet and lay it flat on the workbench. Use a scraping method to evenly coat the paste precursor prepared in step (3) onto the upper surface of the sponge sheet. The coating amount is 200g / m². 2 The coating thickness is approximately 1 mm. After coating, cover with the first 18D intermediate layer sponge sheet and apply a uniform pressure of 0.01 MPa for 5 seconds. Repeat the above coating and covering operations, sequentially stacking the remaining intermediate layer sponge sheets and the last outer layer sponge sheet, forming an alternating stacked structure of 4 interlayer bonding layers and 5 sponge sheets. After all stacking is completed, allow to stand at room temperature for 10 minutes to complete the pre-forming process.

[0052] (5) Heating crosslinking and synchronous foaming and pore formation: The multilayer body pre-shaped by room temperature stacking in step (4) is sent into the hot air circulating drying tunnel for heating treatment. The temperature of the drying tunnel in the first stage is set at 60°C and held for 5 minutes; the temperature of the drying tunnel in the second stage is raised to 110°C and held for 10 minutes. During the holding process, saturated water vapor is introduced into the drying tunnel to maintain the relative humidity of the environment at 60%.

[0053] (6) Compression and Cooling: After the heating and curing in step (5) is completed, the multilayer composite is taken out from the drying tunnel and sent to the flattening and shaping machine, where it is cooled to 30°C by air cooling under a pressure of 0.01MPa. After cooling, a multilayer sponge composite filling core is produced, with a total thickness of 33mm. The filling core is then subjected to a second curing treatment at 40°C for 4 hours.

[0054] (7) Fabric cutting and sewing: Double-sided knitted fabric with a weight of 160g / m² is selected. 2 The fabric is composed of 50% cotton, 5% spandex, and 45% polyester fiber. It has undergone hydrophilic softening and antibacterial / anti-mite treatments. Cut the fabric into one upper piece and one lower piece, each measuring 156cm × 216cm (including seam allowance). Sew the three edges of the upper and lower pieces together with a straight seam, leaving one side open as a filling opening.

[0055] (8) Filling and quilting fixation: The multi-layer sponge composite filling core obtained in step (6) is inserted into the duvet cover shell, laid flat, with accurate corner alignment, and the opening is sewn closed. A single-needle quilting machine is used for wavy quilting, with a quilting spacing of 15cm. High-strength polyester sewing thread with a linear density of 20tex is used for quilting.

[0056] (9) Edge binding and finished product inspection: The edges of the quilted quilt are bound with a binding width of 2cm. Example 4

[0057] A tensile and water-resistant sponge quilt includes a quilt cover fabric and a filling core inside the quilt cover fabric. The filling core is composed of six layers of sponge sheets and interlayer bonding layers disposed between adjacent sponge sheets, stacked alternately in the following manner: sponge sheet - interlayer bonding layer - sponge sheet - interlayer bonding layer - sponge sheet - interlayer bonding layer - sponge sheet - interlayer bonding layer - sponge sheet - interlayer bonding layer - sponge sheet; wherein, the thickness of a single layer of sponge sheet is 10mm, the outermost two sponge sheets are 40D elastic sponge, the middle four layers of sponge sheets are 25D low-density sponge, and the interlayer bonding layer is a porous low-density composite fiber layer with a single layer thickness of 3mm and an average pore size of 20μm; the total thickness of the filling core is 75mm.

[0058] The sponge sheet is made of polyurethane. The 40D elastic sponge is composed of the following components by weight: 100 parts of sucrose-based polyether polyol (DOW VORANOL 800) with a hydroxyl value of 48 mg KOH / g; 28 parts of polymer polyol (DOWVORALUX HN 400) with a solid content of 42%; 48 parts of toluene diisocyanate; 3.0 parts of water; 5 parts of HFC-245fa physical foaming agent; 1.5 parts of silicone oil surfactant (Tegostab B 8681); 0.3 parts of dimethylcyclohexylamine catalyst; 0.15 parts of dioctyltin dimercaptoacetic acid catalyst; 1.2 parts of diisopropanolamine crosslinking agent; 1.5 parts of neopentyl glycol chain extender; 0.8 parts of polycarbodiimide hydrolysis stabilizer; and 1 part of antioxidant (Irganox). 1135) 0.5 parts, polysiloxane-polyether copolymer hydrophobic agent 2.5 parts; 25D low-density sponge is composed of the following substances in parts by weight: 100 parts of sucrose-based polyether polyol (DOW VORANOL 800) with a hydroxyl value of 48 mg KOH / g, 28 parts of polymer polyol (DOW VORALUX HN 400) with a solid content of 42%, 45 parts of toluene diisocyanate, 4.0 parts of water, 7 parts of HFC-245fa physical foaming agent, 1.5 parts of silicone oil surfactant (Tegostab B 8681), 0.3 parts of dimethylcyclohexylamine catalyst, 0.15 parts of dioctyltin dimercaptoacetic acid catalyst, 1.2 parts of diisopropanolamine crosslinking agent, 1.5 parts of neopentyl glycol chain extender, 0.8 parts of polycarbodiimide hydrolysis stabilizer, and antioxidant (Irganox). 0.5 parts of 1135 and 2.0 parts of polysiloxane-polyether copolymer hydrophobic agent.

[0059] The interlayer bonding layer is composed of the following components by weight: 100 parts of water-dispersible closed-cell polyurethane prepolymer emulsion (solid content 48%); 25 parts of cotton fiber (4 mm in length); 6 parts of azodicarbonamide foaming agent; 0.6 parts of zinc oxide foaming activator; 12 parts of starch-grafted sodium acrylate-acrylamide copolymer superabsorbent resin microparticles (particle size 30 μm); 10 parts of β-cyclodextrin; 1.5 parts of fatty alcohol polyoxyethylene ether (AEO-9) nonionic surfactant; 0.8 parts of carbodiimide hydrolysis stabilizer; and 0.4 parts of polyurethane associative thickener (HEUR).

[0060] The preparation method of the tensile and water-resistant sponge quilt in this embodiment includes the following steps: (1) Preparation of sponge sheets: Foaming materials for 40D outer layer sponge and 25D middle layer sponge were prepared separately. All components except toluene diisocyanate and HFC-245fa were added to the mixing vessel in sequence and stirred at 1300 rpm for 15 min at 24℃ to obtain white material composition. HFC-245fa was added to the white material composition and stirred for 50 s. Finally, toluene diisocyanate was added and stirred at 5500 rpm for 6 s immediately. The mixture was quickly poured into the mold, and the mold temperature was controlled at 42℃. The material was allowed to foam and rise freely. The milky whitening time was controlled at 9~11 s and the rising time at 80~90 s. After foaming, the foam was removed from the mold and cured in an oven at 78℃ for 5 h. The cured block sponge was cut into 10 mm thick sheets on a horizontal slicer, and the cutting thickness tolerance was controlled within ±0.3 mm. Two outer layer sponge sheets were cut and four middle layer sponge sheets were cut.

[0061] (2) Surface activation treatment of sponge sheet: The sponge sheet obtained in step (1) is passed through an atmospheric pressure plasma treatment device at a linear speed of 12 m / min and a treatment power of 2.5 kW to uniformly treat both sides of the sponge sheet.

[0062] (3) Preparation of interlayer bonding paste precursor: Weigh each component according to the formula amount, add the water-dispersible closed polyurethane prepolymer emulsion into a planetary mixer, stir at 70 rpm at room temperature, and add cotton fiber, starch-grafted sodium acrylate-acrylamide copolymer superabsorbent resin microparticles, β-cyclodextrin, fatty alcohol polyoxyethylene ether nonionic surfactant, carbodiimide hydrolysis stabilizer and polyurethane associative thickener in sequence. Finally, add azodicarbonamide foaming agent and zinc oxide foaming activator. After all materials are added, continue stirring at 70 rpm for 28 min to ensure that all components are fully mixed and uniform, forming a fine and uniform paste.

[0063] (4) Coating and Stacking Pre-forming: Take the first layer of 40D outer layer sponge sheet and lay it flat on the workbench. Use a scraping method to evenly coat the paste precursor prepared in step (3) onto the upper surface of the sponge sheet. The coating amount is 320g / m 2 The coating thickness is approximately 2.5 mm. After coating, a first 25D intermediate layer sponge sheet is applied and a uniform pressure of 0.02 MPa is applied for 8 seconds. The coating and covering operations are repeated, and the remaining intermediate layer sponge sheets (4 layers in total) and the last outer layer sponge sheet are stacked sequentially, forming an alternating stacked structure of 5 interlayer bonding layers and 6 sponge sheets. After all stacking is completed, the structure is left to age at room temperature for 18 minutes to complete the pre-forming process.

[0064] (5) Heating crosslinking and synchronous foaming and pore formation: The multilayer body pre-shaped by room temperature stacking in step (4) is sent into the hot air circulating drying tunnel for heating treatment. The temperature of the drying tunnel in the first stage is set at 70°C and held for 7 minutes; the temperature of the drying tunnel in the second stage is raised to 125°C and held for 18 minutes. During the holding process, saturated water vapor is introduced into the drying tunnel to maintain the relative humidity of the environment at 75%.

[0065] (6) Compression and Cooling: After the heating and curing in step (5) is completed, the multilayer composite is taken out from the drying tunnel and sent to the flattening and shaping machine, where it is cooled to 38°C by air cooling under a pressure of 0.04MPa. After cooling, a multilayer sponge composite filling core is produced, with a total thickness of 75mm. The filling core is then subjected to a secondary curing treatment at 48°C for 5.5h.

[0066] (7) Fabric cutting and sewing: Warp-knitted elastic fabric with a weight of 240g / m² is selected. 2 The fabric is composed of 80% nylon and 20% spandex, and has undergone moisture-wicking and antibacterial / anti-mite treatments. Cut the fabric into one upper piece and one lower piece, each measuring 226cm x 246cm (including seam allowance). Sew the three edges of the upper and lower pieces together with a straight seam, with a seam width of 1.3cm, leaving one edge as an opening for filling.

[0067] (8) Filling and quilting fixation: The multi-layer sponge composite filling core obtained in step (6) is inserted into the duvet cover shell, laid flat, with accurate corner alignment, and the opening is sewn closed. A single-needle quilting machine is used to perform diamond quilting with a quilting spacing of 25cm. High-strength polyester sewing thread with a linear density of 28tex is used for quilting.

[0068] (9) Edge binding and finished product inspection: The edges of the quilted quilt are bound with a binding width of 2.8cm.

[0069] Tables 1 to 4 show the performance tests of the filling core and the low-density sponge and elastic sponge of the same thickness used in Examples 1 to 4, respectively, for the tensile and water-resistant sponge blankets.

[0070] Overall compressive strength (40% indentation): According to GB / T 10807 standard, the entire filling core (including all sponge layers and bonding layers) is placed on a compression testing machine and compressed at a speed of 100 mm / min to 40% of the original thickness of the sample. The compression load (N) at this time is recorded.

[0071] Overall tensile strength: Prepare dumbbell-shaped specimens (thickness equal to the overall thickness of the filler core) according to GB / T 6344 standard, and test the maximum stress (kPa) at tensile fracture.

[0072] Overall elongation at break: The elongation (%) of the specimen at tensile fracture is measured by testing the entire filling core according to GB / T 6344 standard.

[0073] Overall tear strength: Prepare trouser-shaped specimens by the entire filling core according to GB / T 10808 standard, and test the force (N / cm) required per unit thickness when it tears.

[0074] Compression stress relaxation rate: The entire core is compressed to 50% of its original thickness and held for 24 hours. The stress attenuation percentage is then calculated.

[0075] Impact fatigue resistance: The entire filler core is placed on a fatigue testing machine and repeatedly compressed to 50% of its original thickness at a frequency of 4Hz. After 50,000 cycles, the percentage of thickness loss is measured.

[0076] Rebound rate (overall): After compressing the entire filler core to 50% of its original thickness and then releasing the pressure instantly, the percentage of the rebound height relative to the original compression height is measured.

[0077] Table 1. Performance testing of filling core and sponge in Example 1 Overall compressive strength (40% indentation, N) 168 95 152 +76.8% +10.5% Overall tensile strength (kPa) 185 72 118 +156.9% +56.8% Overall elongation at break (%) 112 186 142 -39.8% -21.1% Overall tear strength (N / cm) 18.5 5.8 9.2 +218.9% +101.1% 75% compression set (%) 3.8 14.2 10.5 -73.2% -63.8% Rebound rate (%) 72 48 42 +50.0% +71.4% 24-hour water absorption rate (%) 32 295 248 -89.2% -87.1% Moisture content (%) after centrifugation and dehydration 21 58 52 -63.8% -59.6% Compression stress relaxation rate (%, 24h) 12.5 28.6 22.3 -56.3% -44.0% Impact fatigue resistance (50,000 compressions, thickness loss %) 4.2 18.5 14.2 -77.3% -70.4% Table 2. Performance testing of filling core and sponge in Example 2 Overall compressive strength (40% indentation, N) 195 108 168 +80.6% +16.1% Overall tensile strength (kPa) 198 82 132 +141.5% +50.0% Overall elongation at break (%) 98 168 128 -41.7% -23.4% Overall tear strength (N / cm) 20.2 6.5 10.8 +210.8% +87.0% 75% compression set (%) 3.2 13.5 9.8 -76.3% -67.3% Rebound rate (%) 68 45 40 +51.1% +70.0% 24-hour water absorption rate (%) 28 282 235 -90.1% -88.1% Moisture content (%) after centrifugation and dehydration 23 56 50 -58.9% -54.0% Compression stress relaxation rate (%, 24h) 10.8 26.5 20.8 -59.2% -48.1% Impact fatigue resistance (50,000 compressions, thickness loss %) 3.6 16.8 12.5 -78.6% -71.2% Table 3. Performance testing of filling core and sponge in Example 3 Overall compressive strength (40% indentation, N) 108 62 98 +74.2% +10.2% Overall tensile strength (kPa) 152 55 92 +176.4% +65.2% Overall elongation at break (%) 135 215 168 -37.2% -19.6% Overall tear strength (N / cm) 16.2 4.2 7.5 +285.7% +116.0% 75% compression set (%) 4.5 16.8 12.2 -73.2% -63.1% Rebound rate (%) 76 52 46 +46.2% +65.2% 24-hour water absorption rate (%) 35 325 268 -89.2% -86.9% Moisture content (%) after centrifugation and dehydration 19 62 55 -69.4% -65.5% Compression stress relaxation rate (%, 24h) 14.2 32.5 25.6 -56.3% -44.5% Impact fatigue resistance (50,000 compressions, thickness loss %) 5.0 21.5 16.8 -76.7% -70.2% Table 4. Performance testing of filling core and sponge in Example 4 Overall compressive strength (40% indentation, N) 152 82 132 +85.4% +15.2% Overall tensile strength (kPa) 172 68 108 +152.9% +59.3% Overall elongation at break (%) 118 195 152 -39.5% -22.4% Overall tear strength (N / cm) 19.2 5.2 8.8 +269.2% +118.2% 75% compression set (%) 4.0 15.2 11.2 -73.7% -64.3% Rebound rate (%) 72 50 44 +44.0% +63.6% 24-hour water absorption rate (%) 30 312 255 -90.4% -88.2% Moisture content (%) after centrifugation and dehydration 22 60 53 -63.3% -58.5% Compression stress relaxation rate (%, 24h) 13.0 30.5 24.2 -57.4% -46.3% Impact fatigue resistance (50,000 compressions, thickness loss %) 4.5 20.2 15.5 -77.7% -71.0% As can be seen from the test data in Tables 1 to 4, in terms of mechanical properties, this invention significantly improves the overall mechanical properties of the sponge filling core through an alternating composite structure of multiple layers of sponge sheets and foamed bonding layers. Compared with a single-density sponge of the same thickness, the filling core prepared by this invention exhibits an overall increase in compressive strength of over 70%, overall tensile strength of over 140%, and overall tear strength of over 87%. Simultaneously, compression set, compression stress relaxation rate, and thickness loss after fatigue compression are all reduced by over 40%, and the resilience rate is increased by over 44%. The mechanical stability and support performance are significantly superior to a single sponge structure. Regarding water absorption, this invention significantly reduces the water absorption rate of the sponge quilt by introducing hydrophobic components into the interlayer bonding layer and controlling the porous structure. Compared to traditional single sponges, the 24-hour water absorption rate is reduced by over 86%, and the moisture content after centrifugal dehydration is reduced by over 54%. Water is more easily removed after washing, reducing the likelihood of mold and deterioration due to residual water absorption, and the washability is fundamentally improved. The tensile and washable sponge quilt prepared by this invention combines excellent mechanical durability and washability, making it suitable for long-term use as household bedding.

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A tensile-resistant and water-resistant sponge quilt, comprising a quilt cover fabric and a filling core inserted into the quilt cover fabric, characterized in that, The filling core is composed of at least two layers of sponge sheets and an interlayer bonding layer disposed between adjacent sponge sheets, which are stacked alternately. The thickness of a single layer of the sponge sheet is 5~20mm; The interlayer bonding layer is a porous low-density composite fiber with a thickness of 2-5 mm and a pore size of 10-50 μm.

2. The tensile and water-resistant sponge quilt according to claim 1, characterized in that, The two outermost sponge sheets are made of 30~60D elastic sponge, while the middle sponge sheet is made of 18~40D low-density sponge.

3. The tensile and water-resistant sponge quilt according to claim 2, characterized in that, The sponge sheet is made of polyurethane and is composed of the following components by weight: 80-120 parts of polyether polyol with a hydroxyl value of 42-56 mg KOH / g, 15-35 parts of polymer polyol with a solid content of 40%-45%, 35-55 parts of toluene diisocyanate, 2.5-4.5 parts of water, 3-8 parts of physical foaming agent, 0.8-2 parts of silicone oil surfactant, 0.15-0.4 parts of amine catalyst, 0.1-0.3 parts of tin catalyst, 0.5-1.5 parts of crosslinking agent, 0.5-2 parts of chain extender, 0.3-1 part of hydrolysis stabilizer, and 1-3 parts of hydrophobic agent.

4. The tensile and water-resistant sponge quilt according to claim 3, characterized in that, The physical foaming agent is selected from any one of cyclopentane, n-pentane, isopentane, or HFC-245fa; the crosslinking agent is selected from any one of diethanolamine, triethanolamine, or glycerol; the chain extender is selected from any one of ethylene glycol, 1,4-butanediol, or diethylene glycol; the hydrolytic stabilizer is selected from any one of carbodiimide compounds or polycarbodiimide; and the hydrophobic agent is selected from any one of polysiloxane hydrophobic agents, fluorinated alkyl acrylate copolymers, or metal stearate salts.

5. The tensile and water-resistant sponge quilt according to claim 2, characterized in that, The interlayer bonding layer is composed of the following substances in parts by weight: A water-dispersible, closed-cell polyurethane prepolymer emulsion with a solid content of 40%~50%, 100 parts; Cotton fiber, length 1~5mm, 10~30 parts; Azodicarbonamide foaming agent, 3-8 parts; Zinc oxide foaming activator, wherein the amount of zinc oxide foaming activator added is 5% to 15% of the weight of the azodicarbonamide foaming agent; Micronized superabsorbent resin microparticles, particle size 10~50μm, 5~15 parts; β-Cyclodextrin, 3-12 parts; Nonionic surfactant, 0.5~2 parts; Additives: 0.5-1.5 parts.

6. The tensile-resistant and water-washable sponge quilt according to claim 5, characterized in that, The micronized superabsorbent resin particles are selected from any one of starch-grafted acrylate copolymers, cellulose-grafted acrylamide copolymers, or polyacrylate superabsorbent resins; the nonionic surfactant is selected from any one of alkylphenol polyoxyethylene ethers, fatty alcohol polyoxyethylene ethers, or sorbitan fatty acid esters; the additives are hydrolytic stabilizers and rheology modifiers, wherein the hydrolytic stabilizer is a carbodiimide hydrolytic stabilizer; and the rheology modifier is any one of hydrophobically modified alkali-swellable acrylate thickeners or polyurethane associative thickeners.

7. A method for preparing a tensile-resistant and water-washable sponge quilt as described in any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Preparation of sponge sheets Weigh each component raw material according to the formula described in claim 3, mix the other components except toluene diisocyanate and physical foaming agent evenly, add physical foaming agent and stir for 30-60s, finally add toluene diisocyanate and stir at high speed of 4500-6000rpm for 3-8s, pour into mold for foaming, and mature at 70-80℃ for 4-8h. Cut the matured block sponge into thin slices with a thickness of 5-20mm on a horizontal slicer. (2) Formulation of interlayer-bound paste-like precursors Weigh each component according to the formulation described in claim 5, put the water-dispersible closed polyurethane prepolymer emulsion into a stirring container, and add cotton fiber, micronized superabsorbent resin microparticles, β-cyclodextrin, nonionic surfactant, hydrolysis stabilizer and rheology modifier in sequence at room temperature. Finally, add azodicarbonamide foaming agent and zinc oxide foaming activator, and stir at a low speed of 40-80 rpm for 20-30 min to form a uniform paste. (3) Coating and stacking pre-form The paste-like precursor obtained in step (2) is coated on the upper surface of the first layer of sponge sheet, with a coating amount of 200~400g / m². 2 The coating thickness is 1~3mm. Cover with a second layer of sponge sheet and apply a pressure of 0.01~0.03MPa to press. If there are multiple layers, repeat the above operation until all sponge sheets are stacked. Let it stand at room temperature for 10~20 minutes to complete the pre-form. (4) Heating and curing molding The stacked preform obtained in step (3) is heated to 110~130℃ and kept at that temperature for 10~20min to allow the closed polyurethane prepolymer to undergo a desealing and crosslinking reaction. At the same time, the azodicarbonamide foaming agent is heated and decomposed to foam evenly. After cooling, a multilayer sponge composite filling core is obtained. (5) Filling and quilting fixation The multi-layer sponge composite filling core obtained in step (4) is inserted into the shell made of quilt cover fabric and fixed by single-needle quilting with a quilting spacing of 15~30cm to obtain a tensile and water-resistant sponge quilt.

8. The preparation method according to claim 7, characterized in that, In step (1), the foaming process parameters are: raw material temperature 22~26℃, mold temperature 35~45℃, milky whitening time 8~14s, and rising time 75~110s.

9. The preparation method according to claim 7, characterized in that, In step (4), the heating process is divided into two stages: the first stage is to keep the temperature at 60~80℃ for 5~8 minutes to allow the paste precursor to penetrate and wet the pores on the surface of the sponge. In the second stage, the temperature is raised to 110~130℃ and held for 10~20 minutes to simultaneously complete cross-linking curing and foaming pore creation.

10. The preparation method according to claim 9, characterized in that, In step (4), after the heating and curing is completed, the multilayer composite is cooled to 30-40°C under a pressure of 0.01-0.05MPa to perform a shaping treatment.